ACE inhibitor lisinopril influence on left ventricular diastolic dysfunction and endothelial response in hypertensive patients with or without chronic heart failure - A. D. Kuimov; O. N. Belyaeva; I. I. Volkova; O. N. Novikova; G. R. Musina; O. G. Kukushkina (Российский кардиологический журнал)
In 20 patients with arterial hypertension (AH), ACE inhibitor lisinopril (dapril) was administered as monotherapy for 11, 6 weeks. Mean age of the participants was 56+/-9, 67 years. Group 1 included 8 patients with chronic heart failure (CHF) symptoms, Group 2 - 12 patients without CHF. In Group 1, mean dapril dose was 19, 38 mg/d, in Group 2 - 9, 85 mg/d. For 4 patients from Group 1 and 1 patient from Group 2, due to monotherapy inefficacy, hypothiazide (12, 5 mg/d) was added. The complex clinical examination included 24-hour blood pressure monitoring (24-hour BPM), left ventricular diastolic function assessment with Doppler echocardiography, endothelial response measurement by D. Celermayer method (1992), and quality-of-life evaluation by international scales. Among patients with AH and no CHF, dilapril monotherapy more effectively decreased systolic and diastolic BP levels, pressure load, in comparison to CHF group. A significant diastolic function improvement was observed in both groups. Endothelial response improved only in non-CHF patients. Quality-of-life improved susbstantially in both groups.